Biological amine (histamine and tyramine) content and its relationship with physical-chemical characteristics of chicha de jora samples prepared in the province of Abancay, Apurímac - Periche Pérez, Julissa (2018)
Chicha de jora, being a spontaneous fermentation drink, does not offer information about the metabolites produced by the microorganisms responsible for fermentation, thus its innocuousness for consumers is unknown. Given this situation, the aim of this study was to determine the content of biogenic amines in samples from the province of Abancay (districts of Abancay and Tamburco) using HPLC, compare these values with the permissible limits and evaluate the biogenic amine content and physicochemical characteristics of “chicha de jora”. Of the 83 samples analyzed, concentrations of up to 37.53 mg/L of histamine and 77.95 mg/L of tyramine were reported. 7% and 12% of the samples from Abancay and Tamburco respectively reported concentrations above the permissible limit of histamine (8 mg/L); and 16% of the samples from both districts reported concentrations above the permissible limit of tyramine (25 mg/L). For the relationship with its physicochemical characteristics, only a significant relationship was found between acidity percentage and histamine content (r = 0.502).